Recovery from the damage of cranial radiation modulated by memantine, an NMDA receptor antagonist, combined with hyperbaric oxygen therapy. Issue 1 (28th June 2022) - Hokama, Yohei; Nishimura, Masahiko; Usugi, Ryoichi; Fujiwara, Kyoko; Katagiri, Chiaki; Takagi, Hiroshi; Ishiuchi, Shogo
Abstract: Background: Radiotherapy is an important treatment option for central nervous system malignancies. However, cranial radiation induces hippocampal dysfunction and white matter injury; this leads to cognitive dysfunction, and results in a reduced quality of life in patients. Excitatory glutamate signaling through N -methyl-d -aspartate receptors (NMDARs) plays a central role both in hippocampal neurogenesis and in the myelination of oligodendrocytes in the cerebrum. Methods: We provide a method for quantifying neurogenesis in human subjects in live brain during cancer therapy. Neuroimaging using originally created behavioral tasks was employed to examine human hippocampal memory pathway in patients with brain disorders. Results: Treatment with memantine, a non-competitive NMDAR antagonist, reversed impairment in hippocampal pattern separation networks as detected by functional magnetic resonance imaging. Hyperbaric preconditioning of the patients just before radiotherapy with memantine mostly reversed white matter injury as detected by whole brain analysis with Tract-Based Spatial Statics. Neuromodulation combined with the administration of hyperbaric oxygen therapy and memantine during radiotherapy facilitated the restoration of hippocampal function and white matter integrity, and improved higher cognitive function in patients receiving cranial radiation. Conclusions: The method described herein, for diagnosis of hippocampal dysfunction, and therapeutic intervention can be utilized to restore some of the cognitive decline experienced by patients who have received cranial radiation. The underlying mechanism of restoration is the production of new neurons, which enhances functionality in pattern separation networks in the hippocampi, resulting in an increase in cognitive score, and restoration of microstructural integrity of white matter tracts revealed by Tract-Based Spatial Statics Analysis.